2023
DOI: 10.1002/ccd.30933
|View full text |Cite
|
Sign up to set email alerts
|

Review of intravascular lithotripsy for treating coronary, peripheral artery, and valve calcifications

Aleksandra B. Gruslova,
Ibrahim H. Inanc,
Mehmet Cilingiroglu
et al.

Abstract: Management of intracoronary calcium (ICC) continues to be a challenge for interventional cardiologists. There have been significant advances in calcium treatment devices. However, there still exists a knowledge gap regarding which devices to choose for the treatment of ICC. The purpose of this manuscript is to review the principles of intravascular lithotripsy (IVL) and clinical data. The technique of IVL will then be compared to alternative calcium treatment devices. Clinical data will be reviewed concerning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
0
0
Order By: Relevance
“…[5][6][7][8] Intravascular lithotripsy (IVL) has emerged as a vessel/lesion preparation strategy to help overcome these issues. 9 The IVL device shatters the calcium within the atherosclerotic plaque using ultrasound (energy) via an angioplasty balloon. A recently completed randomised controlled trial (DISRUPT PAD III) involving 306 lesions (femoropopliteal stenoses or occlusions) treated with either IVL and angioplasty or conventional means (no IVL) showed that IVL resulted in greater procedural success, fewer dissections and comparable rates of major adverse events at 30 days.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Intravascular lithotripsy (IVL) has emerged as a vessel/lesion preparation strategy to help overcome these issues. 9 The IVL device shatters the calcium within the atherosclerotic plaque using ultrasound (energy) via an angioplasty balloon. A recently completed randomised controlled trial (DISRUPT PAD III) involving 306 lesions (femoropopliteal stenoses or occlusions) treated with either IVL and angioplasty or conventional means (no IVL) showed that IVL resulted in greater procedural success, fewer dissections and comparable rates of major adverse events at 30 days.…”
Section: Introductionmentioning
confidence: 99%